ANALISIS HUKUM TERHADAP PERLINDUNGAN SAKSI DAN KORBAN DALAM KASUS TINDAK PIDANA KEKERASAN SEKSUAL - Ente, Faruk Rumbu Raya Rabani (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This research seeks to trace and understand the legal mechanisms relating to the protection of witnesses and victims in cases of sexual violence, as well as the role and effectiveness of judicial institutions in implementing such protection. This research focuses on How is the legal mechanism for the protection of witnesses and victims in cases of sexual violence? What is the role of judicial institutions in providing protection to witnesses and victims in cases of sexual violence? In addition, this study aims to (1) Analyze the legal mechanism of witness and victim protection in criminal cases of sexual violence in Indonesia; (2) Assess the role of judicial institutions in providing protection to witnesses and victims in criminal cases of sexual violence; and Identify obstacles faced in the implementation of legal protection for witnesses and victims and provide recommendations for improvement. This research uses a normative juridical method, with an emphasis on bibliographic writing, to search, examine, and scrutinize the data obtained during the writing. The research findings show that despite an established legal framework, implementation is often hampered by a number of challenges, including a lack of adequate resources and coordination between relevant institutions. The judiciary, as the primary role holder in enforcing the law, has an important responsibility in providing protection to witnesses and victims. In conclusion, this study emphasizes the need for improved coordination, understanding and implementation of mechanisms to protect witnesses and victims of sexual violence within the legal system. These efforts are important to ensure adequate protection for those involved in the legal process, as well as to create a fairer and more effective legal system for all parties involved.